The Effect of Smoking on Long-term Gray Matter Atrophy and Clinical Disability in Patients with Relapsing-Remitting Multiple Sclerosis. Issue 5 (23rd September 2022) - Lie, Ingrid Anne; Wesnes, Kristin; Kvistad, Silje S.; Brouwer, Iman; Wergeland, Stig; Holmøy, Trygve; Midgard, Rune; Bru, Alla; Edland, Astrid; Eikeland, Randi; Gosal, Sonia; Harbo, Hanne F.; et al.
Abstract : Background and Objectives: The relationship between smoking, long-term brain atrophy, and clinical disability in patients with multiple sclerosis (MS) is unclear. Here, we assessed long-term effects of smoking by evaluating MRI and clinical outcome measures after 10 years in smoking and nonsmoking patients with relapsing-remitting MS (RRMS). Methods: We included 85 treatment-naive patients with RRMS with recent inflammatory disease activity who participated in a 10-year follow-up visit after a multicenter clinical trial of 24 months. Smoking status was decided for each patient by 2 separate definitions: by serum cotinine levels measured regularly for the first 2 years of the follow-up (during the clinical trial) and by retrospective patient self-reporting. At the 10-year follow-up visit, clinical tests were repeated, and brain atrophy measures were obtained from MRI using FreeSurfer. Differences in clinical and MRI measurements at the 10-year follow-up between smokers and nonsmokers were investigated by 2-sample t tests or Mann-Whitney tests and linear mixed-effect regression models. All analyses were conducted separately for each definition of smoking status. Results: After 10 years, smoking (defined by serum cotinine levels) was associated with lower total white matter volume (β = −21.74, p = 0.039) and higher logT2 lesion volume (β = 0.22, p = 0.011). When defining smoking status by patient self-reporting, the repeated analyses found an additional association with lower deep gray matter volume (β = −2.35, p = 0.049), and smoking was also associated with a higher score (higher walking impairment) on the log timed 25-foot walk test (β = 0.050, p = 0.039) after 10 years and a larger decrease in paced auditory serial addition test (attention) scores (β = −3.58, p = 0.029). Discussion: Smoking was associated with brain atrophy and disability progression 10 years later in patients with RRMS. The findings imply that patients should be advised and offered aid in smoking cessation shortly after diagnosis, to prevent long-term disability progression.